JENIS-JENIS ANGGREK EPIFIT( Orchidaceae ) DI DESA KOTO TINGGI KECAMATAN RAMBAH KABUPATEN ROKAN HULU - PURNAMASARI, LENNY (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
The study aims to determine the tipes of epiphyticÂ ferm in Orchids (Orchidaceæ) in the village the koto Tinggi Kecamatan Rambah Kabupaten Rokan Hulu. This research has been conducted on November to Desember 2015 with the method survey to the location research directly. Orchid which in be later identified with described the types of Orchids obtained. The result of research in can get one the family (Orchidaceæ), 3 species and 12 individual. As for the types of Orchids obtained which are (Arachis flos-aeris, Cymbidium finlaysonium and Dendrobium crumenatum).